Distinct patterns of seasonal Greenland glacier velocity - Moon, Twila (Geophysical research letters, 2014)
Predicting Greenland Ice Sheet mass loss due to ice dynamics requires a complete understanding of spatiotemporal velocity fluctuations and related control mechanisms. We present a 5 year record of seasonal velocity measurements for 55 marine-terminating glaciers distributed around the ice sheet margin, along with ice-front position and runoff data sets for each glacier. Among glaciers with substantial speed variations, we find three distinct seasonal velocity patterns. One pattern indicates relatively high glacier sensitivity to ice-front position. The other two patterns are more prevalent and appear to be meltwater controlled. These patterns reveal differences in which some subglacial systems likely transition seasonally from inefficient, distributed hydrologic networks to efficient, channelized drainage, while others do not. The difference may be determined by meltwater availability, which in some regions may be influenced by perennial firn aquifers. Our results highlight the need to understand subglacial meltwater availability on an ice sheet-wide scale to predict future dynamic changes